Continuous hydrothermal flow-inspired synthesis and ultra-fast ammonia and humidity room-temperature sensor activities of WO3 nanobricks. (20th January 2020) - Shaikh, Shoyebmohamad F; Ghule, Balaji G; Shinde, Pritamkumar V; Raut, Siddheshwar D; Gore, Shyam K; Ubaidullah, Mohd; Mane, Rajaram S; Al-Enizi, Abdullah M
Abstract: Mesoporous tungsten oxide nanobricks (WO3 NBs) are successfully prepared via a simple and cost-effective hydrothermal synthesis method. The as-synthesized WO3 NBs demonstrate a high sensitivity and selectivity when used for liquid ammonia and humidity sensor activities at room temperature (27 °C). The monoclinic crystal structure has beencorroborated from thex-ray diffraction studies and the specific surface area is estimated to be 38.74 m 2 g −1 . A larger specific surface area has significantly facilitated a fast gas adsorption/desorption process. The WO3 NBs notably exhibite gas sensitivity and selectivity for volatile organic compounds (VOCs) such as ammonia; however, a moderate performance is displayed with different oxidizing and reducing agents at room-temperature, namely: toluene, methanol, ethanol, and acetone. The sensor has offered a commercial potential with an extremely high response (75%), a 15-day operational stability at 100 ppm concentration of ammonia, and a practically remarkable ultra-high 8/5 s response/recovery time. The WO3 NBs-based humidity sensor endows a 32% resistance response at 20% relative humidity, with a quick response/recovery time of 10/8 s; which is due to unique surface architecture of these NBs.